Nonhuman Primate Induced Pluripotent Stem Cells in Regenerative Medicine - Yuehong Wu; Anuja Mishra; Zhifang Qiu; Steven Farnsworth; Suzette D. Tardif; Peter J. Hornsby (Hindawi Limited, 2012)
Among the various species from which induced pluripotent stem cells have been derived, nonhuman primates (NHPs) have a unique role as preclinical models. Their relatedness to humans and similar physiology, including central nervous system, make them ideal for translational studies. We review here the progress made in deriving and characterizing iPS cell lines from different NHP species. We focus on iPS cell lines from the marmoset, a small NHP in which several human disease states can be modeled. The marmoset can serve as a model for the implementation of patient-specific autologous cell therapy in regenerative medicine.